Analysis of psychotropic medicines triazolam, estazolam and alprazolam mixture using high-performance liquid chromatography method - Kravchuk, Yelyzaveta; Marksa, Mindaugas; Zevzikoviene, Augusta; Zevzikovas, Andrejus (ScienceRise: Pharmaceutical Science, 2018)
Poisoning of benzodiazepines, particularly triazolam, estazolam and alprazolam usually is caused by consumption of the drug in bigger doses than prescribed. So, for the fast determination of material caused poisoning, selective and effective methods of analysis are requested. Methods. Benzodiazepines triazolam, estazolam and alprazolam, were chosen for investigation. Analysis was performed using chromatograph „Waters 2695” with a photodiode array detector (Waters 996, at wavelength 200-400 nm range), ACE C18 (2,1 mm x 5,0 cm, 5 μm) chromatographic column, gradient eluent flow (sulfuric acid buffer 0,1% and ACN), eluent flow rate 0,1 ml/min and injection volume of 10 µl. Results. Methodics for identification and quantification of triazolam, estazolam, alprazolam and their mixture was developed using reference solutions. Validated methodic was adapted for identification and quantification of triazolam, estazolam, alprazolam in medicinal products. Conclusions. Selected methodic is suitable for qualification and quantification of the medicinal preparations: ACE C18 (2,1 mm x 5,0 cm, 5 μm) chromatographic column, gradient eluent flow (sulfuric acid buffer 0,1% and ACN), eluent flow rate 0,1 ml/min, injection volume of 10 µl and diode array detector. Mixture of components has been examined and retention times have been stated as follows: alprazolam (13,216 min), estazolam (13,407 min) and triazolam (14,340 min). Retention time upon repetition of analysis have not exceeded the relative error of p <0,05 limitation. Limits of detection of alprazolam is 0,01 µg/ml, estazolam 0,012 µg/ml, triazolam 0,020 µg/ml. Limit of quantification of alprazolam is 0, 022 µg/ml, estazolam 0, 025 µg/ml, triazolam 0, 045 µg/ml